A minor tweak in transplant surgery protocols alters the cellular landscape of the arterial wall during transplant vasculopathy - Mickiewicz, Laura; Zahreddine, Rana; Cormier, Kévin; Peries, Sophie; Del Bello, Arnaud; Laffargue, Muriel; Smirnova, Natalia F. (Frontiers in Transplantation, 2024)
Transplant vasculopathy (TV) is a major complication after solid organ transplantation, distinguished by an arterial intimal thickening, which obstructs the vascular lumen and leads to organ rejection. To date, TV remains largely untreatable, mainly because the processes involved in its development remain unclear. Aortic transplantation in mice, used to mimic TV, relies on highly variable experimental protocols, in particular with regards to the type of anastomosis used to connect the donor aorta to the recipient. While the amount of trauma undergone by a vessel can dramatically affect the resulting pathology, the impact of the type of anastomosis on TV in mice has not been investigated in detail. In this study we compare the cellular composition of aortic grafts from BALB/C donor mice transplanted into C57BL/6J recipient mice using two different anastomosis strategies: sleeve and cuff. While both models recapitulated some aspects of human TV, there were striking differences in the cellular composition of the grafts. Indeed, aortic grafts from the cuff group displayed a larger coverage of the neointimal area by vascular smooth muscle cells (VSMCs) compared to the sleeve group. Aortic grafts from the sleeve group contained higher amounts of T cells, while the cuff group displayed larger B cell infiltrates. Altogether, these data indicate that a seemingly minor technical difference in transplant surgery protocols can largely impact the cellular composition of the graft, and thus the mechanisms underlying TV after aortic transplantation in mice.